"Paraoxonase-1 Aktivnost i Nivoi AOPP-a kod Pacijenata sa Dijabetes Melitusom Tip 2" - OZTURK EMRE, HUMEYRA; KOLDAS, MACIT; EREN, NEZAKET (Journal of Medical Biochemistry, 2025)
Aim: Paraoxonase 1 (PON1) is a calcium-dependent esterase and exerts antioxidant and anti-atherogenic properties. Advanced oxidation protein products (AOPP) are a group of carbonylated protein products showing oxidant-mediated protein damage. This study aimed to determine serum PON1 activities and AOPP concentrations in diabetic patients and to evaluate these parameters in terms of their relationships with diabetes mellitus (DM) and related factors. Methods: A total of 93 patients diagnosed with type 2 DM and 30 healthy controls were enrolled in the study. Serum AOPP levels and PON1 activities were measured spectrophotometrically. Other measurements and clinical/demographic data were ordered for all patients, measured in the routine blood chemistry laboratory, and retrieved from patient files. Results: Serum PON1 activity was significantly lower in patients with DM (31.6 [21.49-48.45] U/mL) compared to controls (41.08 [29.07-54.35] U/mL) (p=0.028). Serum AOPP concentration was significantly higher in diabetic patients (584.6 [453.8-778.6] µmol/L) than in controls (173.9 [98.77-224.1] µmol/L) (p<0.001). PON1 activity negatively correlated with AOPP concentration, and positively with serum HDL-1 levels. AOPP concentration positively correlated with age, weight, HbA1c, glucose, total cholesterol, and LDL-C. A PON1 activity cut-off of ≤25 U/mL predicted DM with a sensitivity of 36.56% and specificity of 90% (AUC: 0.634, p=0.028). An AOPP concentration cut-off of >340 µmol/L predicted DM with a sensitivity of 89.25% and specificity of 93.33% (AUC: 0.965). Both PON1 (OR: 10.821, 95% CI: 1.959 - 59.778, p=0.006) and AOPP (OR: 190.068, 95% CI: 20.102 - 1797.148, p<0.001) were independently associated with DM after adjusting for age, sex, and weight. Conclusions: AOPP and PON1 may play a significant role in the development and progression of DM. Particularly serum AOPP concentrations appear to be distinctive among patients with new-onset DM.